1994
DOI: 10.1099/00222615-40-3-159
|View full text |Cite
|
Sign up to set email alerts
|

Support of Paracoccidioides brasiliensis multiplication by human monocytes or macrophages: inhibition by activated phagocytes

Abstract: Summary. The interaction of human monocytes or monocyte-derived macrophages and yeast-form Paracoccidioides brasiliensis was studied in vitro. Yeast cells were readily ingested by adherent monocytes or macrophages. Multiplication of P. brasiliensis, measured by growth as colony forming units (cfu) on a supplemented medium with good plating efficiency, was greater in monocyte co-cultures compared to the number of cfu obtained from complete tissue-culture medium (CTCM). Multiplication increased with time in macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
47
1
5

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 15 publications
(2 reference statements)
5
47
1
5
Order By: Relevance
“…The results presented here confirm the protective role of IFN-␥ in PCM, as previously demonstrated by several groups (5,10,33). Thus, this cytokine appears to be a major mediator of resistance against P. brasiliensis infection in mice, as it promotes the antifungal activity of the Ms through NO production.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The results presented here confirm the protective role of IFN-␥ in PCM, as previously demonstrated by several groups (5,10,33). Thus, this cytokine appears to be a major mediator of resistance against P. brasiliensis infection in mice, as it promotes the antifungal activity of the Ms through NO production.…”
Section: Discussionsupporting
confidence: 77%
“…Treatment with lymphokine-containing supernatants from mitogen (concanavalin A)-stimulated spleen cells (8) or rIFN-␥ (5)-activated murine peritoneal Ms resulted in potent fungicidal activity against P. brasiliensis. Furthermore, treatment of human monocytes with cytokines, derived from supernatant of ConA-stimulated mononuclear cells and cocultured with the fungus, significantly inhibited multiplication compared to control monocytes (33). However, killing by activated murine Ms could not be abrogated by superoxide dismutase, catalase, or azide, suggesting that the fungicidal mechanism was independent of the oxidative burst products (5).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that monocytes and monocyte-derived macrophages support the intracellular replication of ingested P. brasiliensis (199). However, monocyte-derived macrophages activated by gamma interferon (IFN-y; 300 U/ml, for 3 days) significantly (65 to 95%) inhibited the intracellular replication of ingested P. brasiliensis (199).…”
Section: Macrophagesmentioning
confidence: 99%
“…However, monocyte-derived macrophages activated by gamma interferon (IFN-y; 300 U/ml, for 3 days) significantly (65 to 95%) inhibited the intracellular replication of ingested P. brasiliensis (199). These (231).…”
Section: Macrophagesmentioning
confidence: 99%
“…1 The dimorphic fungus Paracoccidioides brasiliensis, the etiologic agent, is an intracellular parasite and parasitism of host mononuclear phagocytes is the central event in the dissemination of the disease. 2 Natural infections start by inhalation of conidia and/or mycelial fragments of the saprophytic phase. 3,4 The initial pulmonary lesions are asymptomatic in most cases, and may then regress spontaneously, become latent, or disseminate contiguously and/or via the lymphatics.…”
mentioning
confidence: 99%